Measuring. Monitoring. Management. Control - G.A. Anuar; A.A. Trofimov; I.M. Rybakov; S.A. Brostilov (Измерение, мониторинг, управление, контроль)
Background. Electronics, information technology, control, instrumentation, information processing and storage, telecommunications have become the technical base of high technologies. The armament of these means, the completeness of their use determines the appearance modern society. Separately in this row are aerospace object control systems, where increased layout density in combination with high speed and increased functionality, increased reliability in conditions of extreme external influences are added to the general problems electronics development. These additional requirements determined the individual features of the development electronics production and in its fundamental part – sensor equipment. Materials and methods. As a research method, simulation modeling was used, in which the studied sensor is replaced by its model, with which experiments are carried out in order to obtain information about this object. The experiment used specialized Solidworks software to avoid expensive and lengthy test cycles. Results. As a result of modeling, diagrams of temperature distribution fields at critical temperatures were obtained in order to study the effect of these conditions on the parts included in the studied object.